Becoming and being language teacher educators: a collaborative reflexive account - Nguyen M; Qi GY (Taylor and Francis Group, 2024)
In this study we employed reflexivity as a typology and a means to foster our own becoming and being as language teacher educators (LTEs). Specifically, drawing on reflexivity as mutual collaboration, we engaged in duoethnography where we were researcher-participants in each other’s narratives, with the capacity to be reflexive beings. We collaboratively inquired into our own and one another’s professional trajectories, demonstrating how our journeys of becoming and being LTEs were characterised by our social and linguistic identities, our work and interaction with language teachers, and the research and teaching praxis. Findings and discussion advocate a dialogue in the field, acknowledging the dispositions, challenges, and possibilities that reflexivity can offer for LTEs’ trajectories.
Keywords: Duoethnography; reflexivity; language teacher educator(LTE); teacher education